A unified conceptual framework of tasks, skills and competences - Margarida Rodrigues; Enrique Fernández-Macías; Matteo Sostero (European Commission, Joint Research Centre (JRC), 2021)
Skills and competences are frequently invoked by policy-makers in reference to labour market developments and education objectives. However, these concepts have different meanings across academic disciplines such as sociology, economics, and education. This paper proposes a unified conceptual framework for tasks, skills and competences. We start from the concept of task, as the smallest unit of work involved in an economic process. Skills are defined as the ability to perform tasks. Similar tasks are grouped into task domains, which are bundled by employers into jobs. Likewise, similar skills make up skill domains, while competence is the ability to master skills across domains. This framework has two major advantages. First, it provides distinct definitions of relevant concepts and the relations between them. Second, it bridges the socio-economic concepts of skills and tasks, which relate to the labour market, with the education and training literature, which focuses on skill and competence development as learning objectives. We also propose a way to measure the different concepts empirically.
Keywords: 330; Tasks; skills; competences; framework